POTENSI PRODUKSI BIOFUEL DARI BIOMASSA FITOPLANKTON LAUT SPESIES Chlorella vulgaris, Dunaliella salina DAN Spirulina sp., YANG DITUMBUHKAN DALAM NUTRIEN UNGGUL “MSSIP” TERINDUKSI ION LOGAM Fe, Co, DAN Ni - Syahruddin Kasim; Paulina Taba; Indah Raya; Ruslan Ruslan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
Research about composition of superior nutrients, growth parameters, and best method to maximize production of biomass sea phytoplankton, Chlorella vulgaris, Dunaliella salina, and Spirulina sp. has been performed. The nutrients was named as MSSIP which were consist of following compositions: urea fertilizer, Arschat-M nutrient, Fe:Co:Ni metal ions (6 : 3 : 9 : 6 : 3). Methods used were identification and analysis of sea phytoplankton. Determination of optimum growth condition, pure culture, and mass culture were using local raw materials-based engineered nutrients or MSSIP (M. Sjahrul-Syahruddin Kasim-Indah Raya-Paulina Taba). Determination of product density of sea phytoplankton biomass, analyses of carbohydrate content, and lipid biomass were done by using haemocytometer and microscope, Luff Schrol method, and soxhlet method (n-hexane as solvent), respectively. Morphology of phytoplankton was identified by using a digital camera microscope, SZ60/sZ60-61. Furthermore, to understand the effect of metal ions, Fe, Co, and Ni added into MSSIP nutrient, identification of nutrient before and after culturing process were done using XRF-Thermo-Fisher. The results showed that Chlorella vulgaris, Dunaliella salina, and Spirulina sp. were suitable as raw materials to produce biofuel. Those three phytoplankton contained 0,3095 g/L, 0,3782 g/L, and 0,3325 g/L biomass, 32,49%w/w, 31,58%w/w, and 29,81%w/w carbohydrates; and 25,95%w/w, 26,82%w/w and 24,53%w/w lipid, respectively. Best optimum condition of culture were salinity of 30-35%, temperature of 20-30 °C, pH of 8-9, initial density of 2.5 x 104 cell/mL, light exposure of 40 watt, and continuously aerated with CO2. Based on our study, sea phytoplankton, Chlorella vulgaris, Dunaliella salina, and Spirulina sp. have a high potency as source of bioethanol and biodiesel.Keywords: mass culture, superior nutrient MSSIP, sea phytoplankton biomass, Fe, Co, Ni metal ions